Analisis Kebijakan Open Door Policy Jerman Di Tengah Krisis Pengungsi Di Kawasan Eropa Tahun 2015 - Dwipayani, I Dewa Ayu Made Dina; Putri, Penny Kurnia; PrameswarI, Anak Agung Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2022)
This study aims to examine the factors that influence the adoption of the German Open Door Policy. The increasing refugee problem has resulted in the emergence of a refugee crisis in the European region. The foreign policies implemented by European countries have been in the spotlight in the midst of the refugee crisis that occurred. Germany as a refugee receiving country implements an open door policy which is considered a solution to the crisis that hit the European region, whose implementation is considered controversial. Therefore, the researcher analyzes it qualitatively through the perspective of neoclassical realism and foreign policy analysis. The researcher identified domestic and international factors that influenced the decision to take this policy, including demographic conditions, Germany's history, Germany's national interest, Germany's domestic policy regarding refugees, rejection of refugees in a number of countries in Europe, Germany's position in the eyes of the world, laws and regulations, and international agreements.   Keywords: Germany, Neoclassical Realism, Open Door Policy, Refugee Crisis.